AMPLITUDO SENSORY NEURON ACTION POTENTIAL USING AS INSTALLATION OF POLYNEUROPATHY DIAGNOSIS - Kinesya, Billi; Husna, Machlusil; Kurniawan, Shahdevi Nandar; Ridwan, Mochammad (Malang Neurology Journal, 2018)
Background. Polyneuropathy is the pathologic changes and functional disturbances in the peripheral nervous system. These changes manifest as sign and symptoms such as numbness, burning, allodynia, atrophy, and lose of stimulation responses. Diagnosing polyneuropathy can use electrodiagnostic method like electroneuromyography (ENMG). One of the most sensitive ENMG parameters for polyneuropathy is SNAP amplitude which can be measured at Sural Nerve.Objective. The goal of this study is to know whether SNAP amplitude can be used to diagnose polyneuropathy.Methods. The study design is diagnostic test in cross-sectional method.Results. Samples were taken from 108 ENMG medical records of Neurology Department Saiful Anwar General Hospital during the whole 2014. Two variables which are compared are polyneuropathy diagnosis and SNAP amplitude. Fisher test shows significant differences between the two with p = 0.04. Diagnostic test shows sensitivity 68.3%, spesifisity 80%, positive predictive value 97.1%, and negative predictive value 20.5%.Conclusion. There is a significant relationship between SNAP amplitude reduction with the diagnosis of polyneuropathy.